Influence of injection parameters on NOx emission from biodiesel powered diesel engine by Taguchi technique. Issue 8 (2nd July 2020) - Manigandan, S.; Gunasekar, P.; Nithya, S.; Devipriya, J.; Raja, S.; Venkatesh, S.
ABSTRACT: This paper studies the effect of injection parameters on reduction of nitrogen oxide (NOx) emission in a multicylinder diesel engine using Taguchi orthogonal array. To obtain good performance in experiments, we have employed L9 Taguchi array on mixed level fractional design. The engine is fuelled with corn oil methyl ester biodiesel. From the experiment validation, it is found that the urea concentration and the spray angle reduce the production of NOx in the diesel engine. However, it is found that the mixing length does not support the diminution of NOx emission effectively. Additional, ANOVA outcome also reveals that the urea flow rate, urea concentration and the spray angle plays an imperative role in the reduction of NOx emission. The values of the experiments are in accordance with the Taguchi technique.